Perspektif Islam dalam Game Persona 4 Golden: Analisis Karakter, Pesan Moral, dan Pembelajaran - Muhamad Arjun Dewana; Jenuri Jenuri (Edudeena: Journal of Islamic Religious Education)
Abstract: Video games have become a popular medium not only for entertainment but also for conveying moral values. Persona 4 Golden, a standout game, offers a unique experience by integrating elements of psychology and philosophy into its narrative. However, research analyzing video games from an Islamic perspective is still limited. Therefore, this study aims to fill this gap by analyzing the characters, moral messages, and lessons that can be drawn from Persona 4 Golden through the lens of Islam. Narrative analysis method and Islamic moral theory are employed to understand the representation of Islamic values in this video game. The research findings demonstrate the complexity of values such as honesty, loyalty, patience, tolerance, and forgiveness portrayed in the game. Additionally, the study illustrates the importance of communal interests, the improvement of relationships between characters, and the strengthening of social bonds. Thus, this research provides academic contributions and practical insights for game developers who aim to create inclusive content that respects the diversity of players and enriches the gaming experience.